INTENSITAS SERANGAN HAMA TIKUS BELUKAR (Rattus sp) PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) MENGHASILKAN DI KEBUN RAKYAT DESA SUKO AWIN JAYA KABUPATEN MUARO JAMBI - Hayata Hayata; Nasamsir Nasamsir; Robi Aldinardo (Universitas Batanghari, 2021)
Cultivation of oil palm is inseparable from pests. One of the main pests that attack oil palm plants is the rat class which can cause oil palm plantations get a high losses. The aim of this study was to determine the attacktion intensity of the bush rat (Rattus sp) in Oil Palm smallholder at Suko Awin Jaya Village, Muaro Jambi Regency. The research was carried out from February to April 2021 at the oil palm smallholder specifically farmer group“Ridho Ilahi”. The experimental design was unformated trials, and the location was purposively chosen. The location determination of the sample was based on to the initial survey that there was found rats attacktion in this place. Sampling was carried out concurrently at the time fresh fruit bunches harvesting, fruit counting in the bunch, counting the number of fruits eaten by rats, counting good fruit (free from rat pest attacks), and weighing the weight of fresh fruit bunches. Parameters observed were the attacktion level in the land, attacktion intensity, production per hectare, environmental sanitation conditions. The rats attacktion rate of 100%, means that all sample in one stretch of plantation have been attackted by rats, it was indicated by a bite scars on the harvested fresh fruit bunches. The attacktion intensity of the bush rat pest was 23%. The average production was 21.6 tons/hectare/year. The sanitation conditions on the land was partially overgrown with weeds and there were piles of midrib in the area between the certain two path of oil palm tree.